PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN MOTIVASI SEBAGAI VARIABEL MEDIASI (Survei Pada Karyawan PD. BPR Bank Solo) - Karintan Pramitha Puri, Alwi Suddin & Suprayitno (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2016)
This study aimed to analyze the effect of compensation to employee performance, influence of compensation on motivation, motivational influence on employee performance, effect of compensation to employee performance and motivation as a mediating variable. The population in this study were all employees in PD. BPR Solo Bank totaling 38 respondents. Data collection technique used questionnaire and data analysis techniques using validity, reliability test, classic assumption test, path analysis (path analysis) regression 1 and 2. Based on the regression test results show that the compensation does not significantly influence employee performance. Compensation no significant effect on motivation. Motivation significant effect on employee performance. Motivation to mediate between the effect of compensation to employee performance.Keywords: compensation, motivation, employee performance